2022
DOI: 10.1186/s12885-022-10235-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patterns of mutations in RAS/RAF/MEK/ERK/MAPK signaling pathway in colorectal cancer in North Africa

Abstract: Background Our review discuss (i) the findings from analyzed data that have examined KRAS, NRAS and BRAF mutations in patients with colorectal cancer (CRC) in North Africa and to compare its prevalence with that shown in other populations and (ii) the possible role of dietary and lifestyle factors with CRC risk.  Methods Using electronic databases, a systematic literature search was performed for the KRAS, NRAS, and BRAF mutations in CRC patients f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…In preliminary pathological gene pro les, only 38 patients (29.5%) had all WT RAS status, and the majority of patients (69, 53.5%) had WT KRAS/NRAS exons 2 and 3. Low prevalence of KRAS or NRAS exon 4 mutation was found in a retrospective cohort study in North Africa (19), however, potential KRAS or NRAS exon 4 mutations were not assessed comprehensively in our database.…”
Section: Discussionmentioning
confidence: 90%
“…In preliminary pathological gene pro les, only 38 patients (29.5%) had all WT RAS status, and the majority of patients (69, 53.5%) had WT KRAS/NRAS exons 2 and 3. Low prevalence of KRAS or NRAS exon 4 mutation was found in a retrospective cohort study in North Africa (19), however, potential KRAS or NRAS exon 4 mutations were not assessed comprehensively in our database.…”
Section: Discussionmentioning
confidence: 90%
“…43 Similarly to the present study, in North Africa, G12D and G12 C have been revealed in 31.6 and 10.2%, respectively, of all KRAS mutations in patients with CRC. 44 In addition, the G12D mutation is estimated to impact 180,000 patients in the U.S. and Europe, and occurs in 12% of patients with CRC, with ∼80,000 patients in the U.S. and Europe, 45 while G12 C is estimated to impact >70,000 patients in the U.S. and Europe and occurs in 3%–4% of patients with CRC, with ∼20,000 patients in the U.S. and Europe. 45 , 46 …”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that HFeD promoted dysbiosis of the gut bacteria, which led to an increase in SLPI. Mechanically, SLPI released from gut promoted tumorigenesis activated the MAPK signaling pathway, which has been proven to be involved in the pathogenesis 59 , progression 60 and oncogenesis 61 of CRC. Bacterial-derived LPS can activate the MAPK signaling pathway 62 , which is consistent with the abovementioned dysfunction of intestinal barrier, bacterial translocation, and elevated serum LPS.…”
Section: Discussionmentioning
confidence: 99%